Physicochemical, microbiological and oxidative changes during refrigerated storage of N-3 pufa enriched cooked meat sausages with partial nacl substitution - Marchetti, Lucas (2016)
Storage stability of cooked meat sausages with 50 g marine oil/kg and two salt combinations: (1) 14.00 g NaCl/kg and 2.0 g sodium tripolyphosphate (TPP)/kg, (2) sodium reduced formulation with 6.08 g NaCl/kg, 4.92 g KCl/kg and 5.00 g TPP/kg were studied. In addition, effect of BHA or tocopherols as antioxidants was tested. Changes in process yield, purge loss, texture, color, microbial growth and pH during vacuum refrigerated storage were monitored. Partial substitution of sodium did not affect matrix stability, maintaining high process yields and low purge losses (5.5%). The products with marine oil used as fat source resulted in: high PUFA levels and lower risks indicators associated with cardiovascular events. Tocopherols prevented the oxidation process; n-6/n-3 ratio remained unchanged throughout the storage, establishing a natural alternative to BHA. Moreover, the consumption of 15–18 g of this product would cover the recommended daily intake of EPA 1 DHA.